Awareness and Implementation of Solid Waste Management (SWM) Practices - Emerson N. Lalamonan,; Comighud, Sheena Mae (IJRDO- Journal of Educational Research, 2020)
This research used the descriptive-correlational method to determine the level of respondents’ awareness and extent of implementation of Solid Waste Management (SWM) Practices in District 2, Bayawan City Division, Negros Oriental, Philippines for SY 2018-2019 in terms of the areas of segregation, reduce, reuse, recycle, and disposal. The quantitative data were gathered from 81 teachers and 189 students. Also, a survey questionnaire was utilized by the researcher. The statistical tools used in the analysis of the data were weighted mean, mean, and spearman rank correlation. The results revealed that the level of respondents’ awareness on SWM Practices as both perceived by the teachers and students were very high and the extent of implementation of these practices were very great. In addition to this, a significant relationship was noted between the levels of awareness and extents of implementation of SWM Practices. It can be concluded that the level of awareness greatly influenced the extent of implementation of SWM Practices by the teachers and students in District 2, Bayawan City Division.